Digital literacy in social media: A case study - Andreou, Rafaela; Nicolaidou, Iolie (My University, 2019)
Digital literacy skills with respect to the safe use of social media are of prominent importance for adults today, given social media’s high frequency of use and given statistics showing rising percentages of “digital immigrants” who, at the present time, use social media. Previous research was based on people’ self-reports, focused on specific professional groups or students, and did not systematically measure social media literacy. The present case-study attempted to address this gap and answer three research questions: 1) To what extent are citizens literate with respect to social media use? 2) How does people’s perceived competence with social media relate to their social media literacy? 3) What are some factors associated with social media literacy? The main data sources were a demographics questionnaire and a 20-question online-test measuring people’s social media literacy. The emphasis of the test was on the safe use of social media. It included questions relevant to adjusting privacy settings, recognizing and rejecting potentially harmful posts, recognizing the permanency of posts, etc. The instruments were completed by 178 Greek-speaking social media users in the Republic of Cyprus with an average age of 28 years old (SD=8.61, min=19, max=61). Findings suggested that participants’ average social media literacy performance was 83 out of 100 (M=83.34, SD=9.67), therefore relatively high. Factors that related to people’s social media literacy included age, which was negatively correlated with social media literacy (Pearson’s r=-0.27, p<0.01), experience with social media (measured in years), (r=0.18, p<0.05) and frequency of use of social media (measured in hours per day) (r=0.26, p<0.01), which were both positively correlated with social media literacy. People’s perceived competence with social media did not correlate with their performance on the social media literacy test, which provides an indication that people may underestimate or overestimate their competence. Provided that people who overestimate their competence will most probably not actively seek training on staying safe when using social media and provided that the older a person is the lower her level of social media literacy, this case study argues in favor of designing e-learning training addressed to digital immigrants on the safe use of social media. Findings are of value to e-learning designers and e-learning trainers for adults.
Keywords: Digital immigrants; Digital literacy; E-learning; Safe use of social media; Social media